2021
DOI: 10.1016/j.lanwpc.2021.100116
|View full text |Cite
|
Sign up to set email alerts
|

Access route selection for percutaneous coronary intervention among Vietnamese patients: Implications for in-hospital costs and outcomes

Abstract: Background Little is known about rates of access site (transradial (TRI) or transfemoral (TFI)) preference for percutaneous coronary intervention (PCI) and in-hospital costs of patients undergoing these procedures in lower-and middle-countries. Here, we report on access site use, in-hospital costs and outcomes of patients undergoing PCI in Vietnam. Methods Information from 868 patients were included in the cohort of 1022 patients recruited into the first PCI registry in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Despite the proven advantages of TRA, the use of TRA in developing countries has remained relatively low with substantial variations in its geographical uptake. 18 , 19 , 33 , 34 , 35 , 36 The associate concerns include the increased risk of complications and longer procedural times with less experienced interventionists, as well as the learning curve for TRA. Furthermore, poor awareness for quality metrics (e.g., TRA, door-to-balloon time ≤90 min for ST-elevation myocardial infarction, and guideline-directed medical therapy, which are all recommended in clinical practice guidelines) could be another reason associated with the low adoption of TRA in developing countries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the proven advantages of TRA, the use of TRA in developing countries has remained relatively low with substantial variations in its geographical uptake. 18 , 19 , 33 , 34 , 35 , 36 The associate concerns include the increased risk of complications and longer procedural times with less experienced interventionists, as well as the learning curve for TRA. Furthermore, poor awareness for quality metrics (e.g., TRA, door-to-balloon time ≤90 min for ST-elevation myocardial infarction, and guideline-directed medical therapy, which are all recommended in clinical practice guidelines) could be another reason associated with the low adoption of TRA in developing countries.…”
Section: Discussionmentioning
confidence: 99%
“…Previous analyses from the US, Europe, and developing countries suggested that TRA is associated with cost savings mainly because of its lower complication rate and shorter length of stay (LOS) compared to TFA. 14 , 15 , 16 , 17 , 18 , 19 However, these studies may not be applicable to future economic predictions because they were conducted in areas with low TRA implementation and significant variations in geographical uptake; hence, the learning curve of TRA procedures may have influenced the complication rate, LOS, and costs. 20 Furthermore, the economic analysis was conducted with a number of assumptions in the calculation of cost; for example, expenses related to device and pharmacotherapy had to be calculated from the average costs.…”
Section: Introductionmentioning
confidence: 99%
“…This study uses data from a PCI registry conducted from September 2017 to May 2018 in Vietnam National Heart Institute (VNHI), Hanoi, Vietnam. Details of the PCI registry have been previously described [16][17][18][19]. Briefly, the pilot hospital-based registry adapted the data collection forms from a long-standing registry in Australia to collect information on demographic, clinical and procedural information, and outcomes of patients who underwent PCI at VNHI [20,21].…”
Section: Study Settingmentioning
confidence: 99%
“…The number of cardiovascular disease patients increased from 271 million to 523 million, with 197 million people being ischemic heart disease patients [1] . Percutaneous coronary intervention (PCI) has been recognized as an effective treatment for individuals with coronary heart disease (CHD) [2] . Although PCI can alleviate angina pectoris symptoms in patients with CHD, it cannot alter the progression of coronary artery atherosclerosis [3] .…”
Section: Introductionmentioning
confidence: 99%